HCI in business, government and organizations - supporting business : 4th International Conference, HCIBGO 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. Part II /: 4th International Conference, HCIBGO 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. Part II. (2017) - Unknown
No abstract available